Karachi: in the sights of the Pakistani Taliban - Clarke, Ryan (2016)
Karachi, Pakistan’s economic hub, has been hosting key Al-Qaeda figures and is suffering from sectarian violence. Now it appears that the Pakistani Taliban are seeking to establish a stronger foothold amongst young disaffected Pashtuns, with implications for the country.